Can TSH level and premenstrual spotting constitute a non-invasive marker for the diagnosis of endometriosis? - Lena Birke; Dunja M. Baston-Büst; Jan-Steffen Kruessel; Tanja N. Fehm; Alexandra P. Bielfeld (BMC, 2021)
Abstract Background To date, there is no reliable non-invasive marker for the early detection and diagnosis of endometriosis available possibly resulting in a delayed diagnosis and consequently an unnecessary long ordeal for the individual woman. Therefore, the primary objective of the current study was to evaluate whether the combination of a thyroid-stimulating hormone (TSH) level > 2.5 µlU/ml and premenstrual spotting could serve as non-invasive markers of endometriosis. A secondary objective was to determine whether typical symptoms of endometriosis like dysmenorrhea and/or dyspareunia could increase the diagnostic reliability. Methods We conducted a retrospective, case-control study with 167 female patients at the Department of OB/GYN and REI (UniKiD) of the medical center of the University of Düsseldorf, between January 2015 and December 2016. 107 women with surgically confirmed endometriosis were compared to 60 without endometriosis (controls). To evaluate the diagnostic accuracy, we considered sensitivity, specificity and predictive values. In order to assess the association between the non-invasive markers and endometriosis an odds ratio (OR) with a 95% confidence interval was calculated. Results In our cohort, diagnosis of endometriosis with non-invasive markers according to their sensitivity yielded the following ranking: increased TSH level, premenstrual spotting, combination of both previous parameters, addition of dysmenorrhea, addition of dyspareunia and combination of all parameters. Conclusion The existence of endometriosis should be taken into consideration when a patient suffers from thyroid dysfunction and premenstrual spotting. Apart from an increased TSH level, the presence of premenstrual spotting underlines the possible diagnosis of endometriosis with non-invasive markers and therefore, the patient´s history needs to be taken into account carefully. Trial registration The retrospective study was approved by the Ethics Committee of the medical faculty of the Heinrich-Heine University, Düsseldorf, Germany, Registration number Düsseldorf: 5371R (approved: April 04th, 2016). Since the design of the study was retrospective no written informed consent was necessary.